Kendala Guru Dalam Implementasi Kurikulum Merdeka Belajar Dalam Pembelajaran Bahasa Indonesia Pada Materi Teks Deskripsi - Suryaningsih, Ketut; Putrayasa, Ida Bagus; Dewantara, I Putu Mas (Jurnal Penelitian Mahasiswa Indonesia, 2023)
This qualitative descriptive study aims to describe: 1) the teacher's constraints in compiling the Independent Learning Curriculum Teaching Module in Indonesian language learning on descriptive text material. 2) the teacher's constraints in implementing the Merdeka Curriculum in learning Indonesian, especially in descriptive text material and describing research results in a systematically accurate manner, and placing more emphasis on factual data at SMPN 2 Sawan. The subjects of this study were Indonesian language teachers and the objects of this research were the obstacles faced by teachers in compiling the Teaching Modules and implementing the Merdeka Curriculum on descriptive text material on listening and viewing skills. There are four methods used to collect data, namely: 1) observation, 2) interviews, 3) questionnaires, and 4) documentation. The data analysis methods used are: 1) data identification, 2) data reduction, 3) data presentation, and 4) drawing conclusions. The results of this study indicate that: 1) teachers experience obstacles in the form of lack of time in compiling Teaching Modules, 2) selection and preparation of Teaching Module materials, and 3) During implementation the lack of facilities and experience of teachers becomes an obstacle in implementing the Merdeka Curriculum.